Sub-lethal Competition of Joint Predators (Pardosa pseudoannulata and Menochilus sexmaculatus) when Predating Nilaparvata lugens at Different Densities - Siregar, Riza Wardani; Syahrawati, My; Arneti, Arneti; Hamid, Hasmiandy (CROPSAVER, 2023)
Pardosa pseudoannulata and Menochilus sexmaculatus are two predators of the brown planthopper (BPH, Nilaparvata lugens, Hemiptera: Delphacidae) in rice fields. The research aimed to determine the predation and the competition model of P. pseudoannulata and M. sexmaculatus on different BPH densities. This study used a completely randomized design (CRD) factorially. The first factor was the difference in predator species (P. pseudoannulata, M. sexmaculatus, and a combination of predators P. pseudoannulata + M. sexmaculatus), and the second was the difference in N. lugens density (0, 30, 50, and 70 individuals). The treatment was repeated in 4 repetitions. The parameters observed were predatory and competitive behavior, predation rate, body weight gain, and competition model. The research showed that P.pseudoannulata was more aggressive in finding and catching prey than M. sexmaculatus. The more prey provided, the higher the predation rate of the two predators. The combination of them as joint predators has increased the pressure on BPH and the predation rate, although it was still below its potential. Sub-lethal competition occurred between the two predators; it did not affect P.pseudoannulata but affected the behavior and reduced body weight of M. sexmaculatus. The competition between the two predators was not influenced by BPH density but by the intensity of meeting time. Both as joint predators in rice fields are safe and beneficial for BPH control.